Clinical characteristics, management, and outcomes of post COVID-19 mucormycosis in a private ENT hospital in Surat: a retrospective analysis - Mehta, Shailee; Wadia, Farida; Wadia, Mithram; Karulkar, Alok (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Objectives of the study were to assess the age group affected, common presentation, extent of disease of mucormycosis and treatment modalities in post covid patients. Methods: All covid positive patients or recently recovered from covid with features of mucormycosis endoscopically and radiologically were included in this study. All patients that came in the outpatient department were screened using nasal endoscope and CT scans were performed. Patient’s clinical findings and endoscopic findings were correlated with the scans during the pandemic and decision to operate the cases was taken. It was a team approach by otorhinolaryngologist, ophthalmologist, endocrinologist, intensivist and nephrologist. Patients were followed up to 1 year. Results: 65 patients that suggested of mucormycosis clinically, endoscopically, and radiologically were studied. It included 50 (76.9%) males and 15 (23.1%) females and histologically after operating, mucor was present in 44 cases (67.6) and 9 (13.8%) were aspergillosis. Conclusions: Post-COVID mucormycosis was reported after the second COVID wave in India especially after steroid therapies in diabetic patients. Thus, a timely, aggressive, team approach using Modified Denkers or open maxillectomy along with proper intravenous antifungals is the key to survival in such patients.